How to construct an optimal interim report: What the data monitoring committee does and doesn't need to know. (August 2018) - Neaton, James D; Grund, Birgit; Wentworth, Deborah
Background: Data monitoring committees for randomized clinical trials have the responsibility of safeguarding interests of trial participants. To do so, the data monitoring committee must receive reports on safety and efficacy to assess risk/benefit and on trial conduct to ensure that the study can achieve its goals. This article outlines the key components of reports to the data monitoring committee and the important role of the unblinded statistician in preparing those reports. Methods: Most data monitoring committee meetings include open and closed sessions. For each session, there is a report of interim results. The open session is attended by the sponsor and lead investigators, including the statistician(s) responsible for the trial design. These investigators are blinded to the interim treatment comparisons. The closed session is attended by the data monitoring committee members and by the statistician(s) who prepared the closed report. These individuals are unblinded to interim treatment comparisons and therefore are not involved in study design changes. The optimal content of data monitoring committee reports and qualifications of the unblinded statistician(s) are discussed. Reports: Open reports should include responses to data monitoring committee recommendations, a synopsis of the protocol, a review of the protocol history and amendments, and information on enrollment, baseline characteristics, completeness of follow-up, and data quality. The open report is also a vehicle through which the sponsor and investigators should inform the data monitoring committee of relevant external information. Data in the open report are pooled over the treatment groups. The open report should not include data summaries by treatment group. The closed report should include a written summary with references to key tables and figures and methods used to prepare them. Tables and figures should summarize baseline characteristics, follow-up completeness, treatment adherence, and major safety and efficacy outcomes by treatment group. Text summaries should accompany the tables and figures. The data monitoring committee monitoring history (e.g. treatment differences at previous meetings) should be summarized. The unblinded statistician preparing the closed report should be familiar with the protocol and data collection plan and be capable of customizing the report to the current stage of the trial. This includes anticipating questions that may arise during the data monitoring committee review and pro-actively including data summaries to address these questions. Conclusions: There is considerable variation in the quality of open and closed data monitoring committee reports. Open and closed data monitoring committee reports should be concise, up to date, and informative. To achieve this, unblinded statisticians responsible for preparing closed data monitoring committee reports should be familiar with the statistical methods, the trial protocol, and the data collection plan. They should be capable of anticipating questions from the data monitoring committee and responding to requests for additional analyses.